Virtual Onboarding Goes Green: Studi Naratif tentang Integrasi Keberlanjutan dalam Proses Rekrutmen Digital - Burhanuddin, Burhanuddin (PT Maju Malaqbi Makkarana, 2025)
This study examines the integration of sustainability principles into the virtual onboarding process through a qualitative narrative study approach. Analysis of five multinational companies and interviews with 15-20 stakeholders revealed that while 78% of companies have adopted digital practices such as e-documents and virtual training, only 20% explicitly measure their environmental impact. The findings suggest three main benefits: (1) a 63% reduction in paper use and 45% in carbon emissions, (2) an increase in employer branding of up to 30% for consistent companies, and (3) the formation of environmental awareness in new employees. However, challenges such as resistance to change, infrastructure limitations, and lack of measurement standards hinder optimal implementation. This study contributes a new conceptual model that links operational, social, and environmental dimensions, while recommending the development of standard metrics, cross-generational training, and stronger integration with sustainability reporting. The study results enrich the Sustainable HRM literature by offering a framework for implementing virtual onboarding that is aligned with the SDGs, especially in the context of digital transformation in the post-pandemic era.